Engagement and effectiveness of digitally enabled behavioural change support for people living with type 2 diabetes. (7th October 2020) - Kar, Partha; Goward, Charlotte; Whitman, Michael; Davies, Mark; Willner, Tamara; Shaw, Ken
Abstract: People living with type 2 diabetes are usually offered diabetes structured education, brief diet and lifestyle advice, or referral to weight management services. These are delivered in a face‐to‐face setting traditionally, but attendance and outcome data are inconsistent. Digital alternatives provide a different approach, but outcomes and engagement are poorly understood. This study aims to strengthen this evidence by evaluating a digital lifestyle change programme. Data were analysed from participants referred as an alternative to face‐to‐face weight management or structured education courses. They were adults living with type 2 diabetes, with a mean baseline BMI of 35.9kg/m 2 (SD ±6.7). Weight data were collected using digital weighing scales, and the participants' general practitioners collected HbA1c data. Engagement data were collected through interactions with educational articles, tracking devices, and support from peers or a health coach. In total, 144 participants started the programme, and 94 (65.3%) submitted weight readings after 12 months. Of these, 60.6% achieved over 5% total body weight loss, and 28.7% achieved over 10% total body weight loss. The analysis found 41/144 (28.5%) participants returned to their general practice for a blood test, and 39% reduced their HbA1c to below 48mmol/mol. A higher number of interactions with the application was associated with greater weight loss. This evidence supports the effectiveness of digital behaviour change interventions, using structured education and weight management advice. Findings provide information on engagement with these programmes, suggesting a potential association between programme engagement and weight loss. Copyright © 2020 John Wiley & Sons.